Compromise of thermoelectric and mechanical properties in LiSbTe2 and LiBiTe2 alloyed SnTe. (1st June 2022) - Guo, Fengkai; Zhu, Jianbo; Cui, Bo; Sun, Yuxin; Zhang, Xinghong; Cai, Wei; Sui, Jiehe
Abstract: As a kind of promising medium-temperature thermoelectric materials, SnTe has been widely studied in recent years. Herein, we investigate the effect of LiSbTe2 and LiBiTe2 alloying on the thermoelectric and mechanical properties of SnTe. Hall effect measurement and DFT calculation show that both LiSbTe2 and LiBiTe2 alloying induce band convergence, optimizing the electrical transport properties. Nevertheless, the excessive narrowing of band gap caused by LiBiTe2 alloying deteriorates the high-temperature performance significantly. Numerous nano-precipitates and Li-rich nano-domains are formed and play important roles in enhancing phonon scattering. Furthermore, via introducing resonant state by Indium doping, relatively high PF ave of 19.54 µW cm −1 K −2 and ZT ave of 0.64 from 300 K to 873 K are achieved in Sn0.99 In0.01 Li0.125 Sb0.125 Te1.25 sample. However, behind the high thermoelectric performance is the sacrifice of mechanical properties. The fracture toughness falls off a cliff in heavily alloyed sample due to the high density of point defects and nanostructures within the matrix, which greatly increases the risk of fracture under external force or thermal stress during processing or service. This work proposes that the compromise between thermoelectric properties and mechanical properties should be paid attention to during heavily alloying, especially for those materials with inherent poor mechanical performance. Graphical abstract: Image, graphical abstract